2021
DOI: 10.1016/j.mtbio.2021.100131
|View full text |Cite
|
Sign up to set email alerts
|

Altered electrochemical properties of iron oxide nanoparticles by carbon enhance molecular biocompatibility through discrepant atomic interaction

Abstract: Recent advancement in nanotechnology seeks exploration of new techniques for improvement in the molecular, chemical, and biological properties of nanoparticles. In this study, carbon modification of octahedral-shaped magnetic nanoparticles (MNPs) was done using two-step chemical processes with sucrose as a carbon source for improvement in their electrochemical application and higher molecular biocompatibility. X-ray diffraction analysis and electron microscopy confirmed the alteration in single-phase octahedra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…We employed the SWV technique owing to its propensity to eliminate non-faradic currents [ 33 ] that are routinely encountered by amine-terminated MNPs, as indicated by the voltammograms in Figure 2 and Figure 3 [ 34 , 35 , 36 ]. Conferring the MNPs with electroactive properties was carried out by conjugation with ferrocene (Fc), which provides an easily monitored reversible one-electron oxidation of ferrocenium, Fc Fc+ + e− [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…We employed the SWV technique owing to its propensity to eliminate non-faradic currents [ 33 ] that are routinely encountered by amine-terminated MNPs, as indicated by the voltammograms in Figure 2 and Figure 3 [ 34 , 35 , 36 ]. Conferring the MNPs with electroactive properties was carried out by conjugation with ferrocene (Fc), which provides an easily monitored reversible one-electron oxidation of ferrocenium, Fc Fc+ + e− [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, zebrafish, as an emerging model to investigate the potential toxicity, has been used successfully to assess the potential risks induced by the IONPs. The result showed that carbon-modified α-Fe 2 O 3 significantly reduced oxidative stress and apoptosis, which had higher biocompatibility than Fe 3 O 4 [ 47 , 48 ] .
Fig.
…”
Section: Applications Of Ionps In Animal Modelsmentioning
confidence: 99%
“…[115,196,197] For example, high theoretical capacitance, versatile synthesis methods, and economical as well as environmentally sustainable. The theoretical capacitance is calculated using the relation between the molar mass of material (M), working potential window (V), the number of electrons transferred during redox reactions (n), and Faraday's constant (F = 96,485 C/mol), which is stated as, C = n×F/M × V. [198,199] TMOs have high theoretical specific capacitance, such as ruthenium oxide (RuO 2 = 2000 F g −1 ), [200] manganese oxide (MnO 2 = 1370 F g −1 , Mn 3 O 4 = 1264 F g −1 ), [201,202] iron oxide (Fe 2 O 4 = 3625 F g −1 ), [203] nickel oxide (NiO = 2573 F g −1 ), [204] cobalt oxide (Co 3 O 4 = 3560 F g −1 CoO = 4292 F g −1 ), [205,206] copper oxide (CuO = 1800 F g −1 ). [207] These values are significantly higher than carbon allotropes, a commonly used supercapacitor material.…”
Section: Properties and Charge Storage Mechanism Of Tmosmentioning
confidence: 99%